1985
DOI: 10.1093/infdis/151.4.589
|View full text |Cite
|
Sign up to set email alerts
|

IgG Proteolytic Activity of Pseudomonas aeruginosa in Cystic Fibrosis

Abstract: To study how fragmented IgG antibodies might arise within the respiratory secretions of individuals with cystic fibrosis (CF), we screened protease extracts from CF polymorphonuclear leukocytes and mucoid and nonmucoid transformants of Pseudomonas aeruginosa from patients with CF for IgG proteolytic activity. All strains of P. aeruginosa tested exhibited IgG proteolytic activity. Incubation for 7 hr at 37 C was required to demonstrate generation of free Fc gamma immunoreactivity. Further analysis of these clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(43 citation statements)
references
References 21 publications
2
40
0
1
Order By: Relevance
“…This hypothesis is supported by experiments showing degradation of IgG by PA elastase in vitro (13,14) and fragmentation of PA LPS IgG antibody from bronchial lavage fluid of CF patients in vivo (1 1).…”
mentioning
confidence: 80%
“…This hypothesis is supported by experiments showing degradation of IgG by PA elastase in vitro (13,14) and fragmentation of PA LPS IgG antibody from bronchial lavage fluid of CF patients in vivo (1 1).…”
mentioning
confidence: 80%
“…[38][39][40] Also, a number of microorganisms express immunoglobulin-degrading proteases that have been implicated as virulence factors in aiding bacterial colonization. 8,41,42 Other examples of bacterial IgG-degrading proteases include Streptococcal SpeB that cleaves IgG in the upper hinge, 43,44 a Pseudomonas elastaselike enzyme, 45 Mirabilysin of Proteus mirabilis, 46 and Trepolisin of Treponema denticola.…”
Section: Proteolytic Cleavage Of Igg In the Hinge Regionmentioning
confidence: 99%
“…9 Indeed, only limited data exist for the presence of IgG breakdown products in biological samples and those were primarily limited to severely inflammatory settings and focused on Fab and F(ab') 2 products. [57][58][59] It can only be speculated whether localized secretion of IgGdegrading proteases represents a mechanism to quell the inherent inflammatory potential of antibodies. We and others have had our attention drawn to the group of proteases that are expressed by invasive and pathological cells, e.g., tumor cells and bacteria, although enzymes from non-pathological sources, e.g., neutrophil elastase and other human extracellular proteases, might also contribute to IgG breakdown.…”
Section: Proteolytic Cleavage Of Igg In the Hinge Regionmentioning
confidence: 99%
“…However, our group and others have shown that several proteases secreted or expressed in environments where Igs are present can cleave Igs in the hinge region, resulting in a number of cleavage products, including Fab or F(abЈ) 2 (1)(2)(3). These fragments retain the ability to bind to their respective epitopes but lose Fcmediated effector functions that are dependent on Fc domain interactions with Fc receptors, complement, etc.…”
mentioning
confidence: 99%
“…The matrix metalloproteinases (MMPs) 3 matrilysin (MMP-7) and stromelysin-1 (MMP-3) were reported to cleave all subclasses of human IgG in a step-wise process (4). Certain bacterial proteases have been shown to possess strict selectivity for mammalian IgGs (8 -10) The IgG-degrading enzyme of Streptococcus pyogenes (IdeS) specifically cleaves human IgG1 between glycine 236 and glycine 237 (EU numbering) (11) in the lower hinge (1,9,12).…”
mentioning
confidence: 99%